Energetics of middle-distance running performances in male and female junior using track measurements - Billat, V.; Lepretre, P.-M.; Heugas, A.-M.; Koralsztein, J. P. (Japanese Journal of Physiology, 2004)
The aim of this study was to determine the energetic factors of middle-distance running performance in junior elite runners according to gender and by using measurements from on-track performances. Fifteen elite runners (8 males and 7 females) were investigated by means of an incremental test and an all-out run over 600 m performed with a 2-d interval. We calculated (1) the aerobic maximal power (Er max aero, in W kg-1), including VO2 max and the delay of attainment of VO2 max in the 600 m run; (2) the anaerobic power (Er max anaero), i.e., the oxygen deficit (J kg-1) divided by the duration of the 600 m run. Despite the difference in race duration (87 ± 3 vs. 102 ± 2 s), the 600 m run was made at the same relative value of the velocity associated with VO2 max (vVO2 max) in males and females (121.6 ± 7 vs. 120 ± 8% VO2 max, p = 0.7). Er max aero explained most of the variance in the performance (the personal best performed 8 weeks later) between genders: 65 and 79% over 800 m (T800) and 1,500 m (T1,500). For females, Er max aero explained most of the variance of T1,500 (r2 = 0.66), and Er max anaero improved this prediction (r2 = 0.84). No energetic factor predicted the performance on 800 m run in males. In elite junior athletes, the energetic model with individual data measured over an all-out 600 m performed on a track, provides an explanation for most of the variance in middle-distance running performances between genders. The distinction between aerobic power and anaerobic power allowed an improvement in the prediction of middle-distance running performances.